Manual de procedimientos para la empresa Servitubos, en la ciudad de Guayaquil, año 2014 - Mora Macias, Patricia Mirella (2014)
This paper is based on the design and development of a procedures manual for the company Servitubos, in the city of Guayaquil, where processes, standards and policies to improve the current situation of the company are described, and establishing a basic, simple and useful document detailing the different types of procedures to be performed by employees for the implementation of its activities is provided, and thus have an essential and strategic tool to achieve high performance of staff and avoid duplication of effort, lack of hierarchy level and the waste of time and resources. The implementation of the procedures manual will maintain an updated procedures that run in different areas of the company registration and help in strengthening its organizational structure.